Measurement of the production and lepton charge asymmetry of [Formula: see text] bosons in Pb+Pb collisions at [Formula: see text] with the ATLAS detector - ATLAS Collaboration; Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; et al. (The European physical journal. C, Particles and fields, 2015)
A measurement of [Formula: see text] boson production in lead-lead collisions at [Formula: see text] is presented. It is based on the analysis of data collected with the ATLAS detector at the LHC in 2011 corresponding to an integrated luminosity of 0.14 [Formula: see text] and 0.15 [Formula: see text] in the muon and electron decay channels, respectively. The differential production yields and lepton charge asymmetry are each measured as a function of the average number of participating nucleons [Formula: see text] and absolute pseudorapidity of the charged lepton. The results are compared to predictions based on next-to-leading-order QCD calculations. These measurements are, in principle, sensitive to possible nuclear modifications to the parton distribution functions and also provide information on scaling of [Formula: see text] boson production in multi-nucleon systems.